Alimentación familiar: una mirada a la cotidianidad en un barrio de clase media en Cali (Colombia) - Quintero Angel, David (Sociedad y Economía, 2008)
Based on a survey, this paper analyses some aspects of the system of customary feeding practices of families in a middle-class neighbourhood of Cali. This paper is primarily an effort to describe and analyze some aspects related to the interactions among members of the household before, during and after a meal.